Estimation of higher-order spatial autoregressive panel data error component models - Harald Badinger; Peter Egger (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper develops an estimator for higher-order spatial autoregressive panel data error component models with spatial autoregressive disturbances, SARAR(R,S). We derive the moment conditions and optimal weighting matrix without distributional assumptions for a generalized moments (GM) estimation procedure of the spatial autoregressive parameters of the disturbance process and define a generalized two-stages least squares estimator for the regression parameters of the model. We prove consistency of the proposed estimators, derive their joint asymptotic distribution, and provide Monte Carlo evidence on their small sample performance.
Keywords: C13; C21; C23; 330; Higher-order spatial dependence; generalized moments estimation; two-stages least squares; asymptotic statistics; Schätztheorie; Region; Panel; Autokorrelation; Fehlerkorrekturmodell; Momentenmethode; Theorie